(untitled) (R&E-SOURCE, 2014)
Some years ago in teaching of mathematics we had a certain amount of Dynamic Geometry software applications that offered some options in the design of teaching-learning activities. And we could choose the software according to the task and its objectives. This is so because the construction philosophy was different for each application, and thus the knowledge they foster. Today, the trend is that only one of such applications will be at hand, and the only reason is that it is for free. We stand that there is not a dynamic application better that the other, their use should depend on the task at hand and the learning objectives we want to achieve. We will illustrate this with two teaching-learning activities developed with GeoGebra and The Geometer’s Sketchpad and highlight the main features of each and the knowledge students learn and put into action using the software. The two tasks are: • A problem in which the solver has the need of adjusting a curve to a set of points without using a statistical tool. • An activity aimed to foster the concept of iteration in fractals.